Implementasi Algoritma Exclusive OR (XOR) Dalam Pengembangan Aplikasi Chat Berbasis Android - Pujo Hari Saputro (Jurnal Informatika, 2023)
Android is an operating system that is widely used in this modern era. This is inseparable from Android features that are increasingly being developed to facilitate the user experience. Along with these developments, security problems also arise when exchanging information or data. Security is an important aspect of the development of modern information technology era, so the development of the branch of science that studies data security or known as cryptography. This study aims to design and build a secure chat application based on Android and implement the XOR algorithm. This algorithm is used to secure information so that it cannot be read before it reaches the recipient. The calculation of this algorithm generates a random message (ciphertext) that can only be read by the recipient. The result of this search is a chat application in which there is a security feature where the recipient must enter the same key as the sender in order for the message to be read. Testing of this application is done by sending a message then entering the same key between sender and receiver.